(untitled) (Marketing Journal, 2026)
Abstract The article analyzed the mechanisms of activity diversification in increasing the investment potential of industrial enterprises. The study examined the economic essence of diversification and its impact on financial stability, risk distribution, and cash flow stabilization. Based on the example of oil and fat industry enterprises, the role of product and raw material diversification in enhancing investment attractiveness was assessed. Internal resources and external factors were systematized through SWOT analysis. The findings demonstrated that diversification decisions based on economic calculations, market analysis, and risk assessment contributed to strengthening the investment potential of enterprises. Keywords: diversification, investment potential, investment attractiveness, strategic management, risk management, financial stability, innovative development, synergy effect, capital attraction, enterprise value, portfolio theory